Social Marketing Program for Online Chili Market: ‘Buy Fresh Chili Directly From Farmers’ to Improve the Welfare of Chili Farmers in Ciawi District - Lusia, A; Juliana, A (KnE Social Sciences, 2018)
Chili is a vegetable that is most widely grown by farmers in Indonesia. The amount of land planted with chili in 2010 was 237 520 hectares, or more than 20% of the total land used for growing vegetables (Investor, 2013). Chili farmers in the Ciawi District are a part of the Pondok Menteng farmers group that is led by Mr. Haji Misbah. The Pondok Menteng farmers group is located in the village of Pondok Menteng, District of Ciawi, Bogor. The average Ciawi farmers only finish Junior High School. Their educational background affects their decision-making in the process of selling their goods. The farmers want their harvest to sell as quickly and easily as possible, so many farmers rely on middlemen to sell their goods. The middlemen offer ease of transaction to the farmers, on some occasion farmers can even get the money before the farmers finish harvesting, educational background influences the process of counting expenses during the planting, consequently farmers are only counting the biggest expenditure such as fertilizer, water and pest management to determine the selling price. Based on this, it can be concluded that a social marketing program is needed to educate farmers. One of the social marketing program that can be done is to teach the farmers how to sell their goods online. Keywords: social marketing, social marketing program, chili farmer, educate farmer, selling goods online